Wilms' tumour: Determinants of prognosis in an African setting - Akinfenwa Taoheed Atanda; Lofty-John Chuhwuemeka Anyanwu; Oladoyin Jareenat Atanda; Aminu Mohammad Mohammad; Lawal Barau Abdullahi; Aliyu Umar Farinyaro (Wolters Kluwer Medknow Publications, 2015)
Background: The few studies available in the literature on Wilms' tumour (WT) from sub-Saharan Africa have reported a dismal outcome for children with the tumour. This study evaluated the risk factors that have been correlated with outcome in the literature and compare these with outcome among our patients. Materials and Methods: Cases of histologically confirmed WT between 2009 and 2013 in a tertiary hospital in Northwestern Nigeria were evaluated for gender, age, laterality, symptoms, duration before presentation, stage at presentation, histologic subtype and p53 mutation. These were then correlated with outcome. Results: Totally, 30 cases of WT were diagnosed with mean age of 4.8 ± 1.9 years; and male:female ratio of 2:1. No statistically significant relationship with outcome was found for gender (P = 0.138) or histologic subtype (P = 0.671). The most significant variables which positively influenced the outcome were presentation at earlier stages (P = 0.007) and completion of therapy (P = 0.0007). p53 mutation was seen in 3 (16.7%) of 18 cases and was not associated with a poor outcome (P = 0.089). However, 2 of the 3 cases presented in Stage IV and none of them survived the 1 st year. Conclusion: This study shows that even though p53 mutation was associated with a more aggressive phenotype, the most significant determinants of a good outcome among patients in a developing country like ours is non-blastemal dominant histologic subtype, early stage at presentation and completion of therapy.